La mobilité des familles tsiganes françaises à l’épreuve de la gestion politique de l’espace. Stratégies et résistances - Céline Bergeon (Cybergeo, 2014)
This paper deals with the impact of public policies regarding authorized camping for Gypsy families in France. It shows how these families circumvent the legislation and adapt their practices in order to perpetuate their mobility. Drawing on multiple interviews combined with other sources of data, a cartography of several individuals’ mobility is presented. Strategies implemented in response to a challenging legislation regarding Gypsies mobility are then explained and discussed.